Adenoviral transgene delivery provides an approach to identifying important molecular processes in inflammation: evidence for heterogenecity in the requirement for NFκB in tumour necrosis factor production. (1st November 2000) - Foxwell, Brian M J; Bondeson, Jan; Brennan, Fionula; Feldmann, Marc
Abstract : The success of anti-tumour necrosis factor (TNF) treatment, either using antibodies or soluble receptors, has defined TNF as a major factor of the inflammatory response in rheumatoid arthritis (RA). As a result of this success, much attention has been devoted to understanding the molecular mechanisms by which TNF expression and activity is elicited and controlled. By understanding these pathways, it is hoped that key elements of the molecular pathology associated with RA will be uncovered and, as a result, new targets for therapeutic intervention will be identified. However, studying the cell and molecular biology of model systems for RA, such as primary human macrophages, or tissue from rheumatoid joints may present technical problems. In an attempt to overcome this, we have investigated the use of adenovirus as a means of delivering transgenes by which different intracellular pathways can be modulated and examined. Our data show that adenovirus can be successfully used to efficiently deliver transgenes to primary human macrophages and RA joint tissue. Using a virus encoding IκBα, the natural inhibitor of NFκB, we show that the requirement for the transcription factor is not universal, but is dependent on the nature of the stimulus. Furthermore, while NFκB is of importance for the expression of TNF and other pro-inflammatory cytokines (for example, interleukin 6) and the destructive matrix metalloproteinases, this factor is not required for the expression of anti-inflammatory cytokines interleukin 10 and interleukin 1 receptor antagonist.